Co-prescribing naloxone does not increase liability risk. Issue 4 (1st October 2016) - Davis, Corey S.; Burris, Scott; Beletsky, Leo; Binswanger, Ingrid
ABSTRACT: The opioid overdose epidemic claims the lives of tens of thousands of Americans every year. Opioid overdose is reversible by the administration of naloxone, a pure antagonist now available in formulations specifically designed and labeled for layperson use. Despite broad support for layperson access to naloxone from professional organizations, health officials, and clinical experts, qualitative studies suggest that some providers have concerns about legal risks associated with naloxone prescribing, particularly co-prescribing naloxone to pain patients. Such concerns are unfounded. The legal risk associated with prescribing naloxone is no higher than that associated with any other medication and is lower than many. Additionally, laws in a majority of states provide explicit legal protections for providers who prescribe or dispense naloxone, in many cases extending this protection to prescriptions issued to friends, family members, and others. In this large and increasing number of states, the liability risk of prescribing or dispensing naloxone in good faith to a patient at risk of overdose (or, in states where such prescribing is permitted, to an associate of such a patient) is either extremely low or absent entirely. Where a prescriber determines, in his or her clinical judgment, that a patient is at risk of overdose, co-prescribing naloxone is a reasonable and prudent clinical and legal decision. No clinician should fail or refuse to issue such a prescription based on liability concerns.